Uplift Test and Design Method for Bearing Capacity of Isolated Spread Concrete Foundation Slab with Large Width-to-Height Ratio - Yuanqi Li; Xiaoliang Qin; Jinhui Luo; Meng Xiao; Cong Hua (Advances in Civil Engineering)
This paper is focused on the experimental study and numerical simulation of isolated spread concrete foundation slab with a large width-to-height ratio (in short ISCFS-LWR) to investigate the failure modes and uplift bearing capacity, as well as the design method of uplift capacity. First, a total of 16 isolated spread concrete foundation slabs with the width-to-height ratio varied from 1.5 to 4 and the hypotenuse slope varied from 10° to 30° were tested under uplift load. Based on the test results, effects of the width-to-height ratio and the hypotenuse slope on uplift bearing capacity of ISCFS-LWR were analyzed and discussed. Then, several numerical models were built using the finite element software ABAQUS and the results of numerical analysis agreed well with the test results. Furthermore, the cross-sectional performance of ISCFS-LWR was studied, and the coefficients of internal force arm were also evaluated further using previous validated numerical models. To obtain the suggested design method of uplift capacity for the foundation slab, effective width correction coefficient k and slope correction coefficient j were introduced to propose a design formula. Finally, the proposed design method was applied to a practical engineering, and the economic indicators obtained from the suggested design method were compared with that from the original design method. The results of this paper showed that the correction coefficient jsks based on numerical analysis agreed well with the recommended correction coefficient jk, and the error was between 1% and 3.4%, by which the reasonability of the proposed design method of uplift capacity for ISCFS-LWR has been proved. It can also be found that the economic benefits of the practical engineering in this paper were obvious due to the suggested design method, and this paper can provide a reference for other engineering practices and the further research work on ISCFS-LWR.